(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Formation of "media literacy and information literacy" among citizens should be considered as an issue that cannot be postponed. This issue has arisen due to the development of the information society. However, considering it as a process related to modern information technology, there are many debates about representatives of which field should teach this subject. Specifically, as is typical, information technology teachers claim to teach this subject. Nevertheless, how correct is this? In fact, the science of "Media literacy and information literacy" is a cultural, historical, spiritual and social process in its essence. Because, in human evolution, communication, attitude, writing, knowledge, literature and visual arts are analyzed in terms of influence on personal thinking and worldview. Because the information society is rapidly developing, not only is its form changing, but its sphere of influence also is becoming more complex and determines the prospects of society.